True or False (1)

Is it true that there exists positive integers such that: a 2 + b 2 + c 2 = a 2 b 2 \large a^2+b^2+c^2=a^2b^2

True False

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Brian Moehring
Aug 12, 2018

The statement is False. \boxed{\text{False.}} To show this, we will prove the stronger [at least superficially] statement: There is no nonzero integral solution to a 2 + b 2 + c 2 = a 2 b 2 , \text{There is no nonzero integral solution to }\, a^2 + b^2 + c^2 = a^2b^2, by repeatedly using the well-known fact n 2 { 0 ( m o d 4 ) , if n is even 1 ( m o d 4 ) , if n is odd . n^2 \equiv \begin{cases} 0 \pmod{4}, & \text{ if } n \text{ is even} \\ 1 \pmod{4}, & \text{ if } n \text{ is odd}\end{cases}.

Suppose there is a nonzero integral solution ( a 0 , b 0 , c 0 ) . (a_0,b_0,c_0). Then the equation can be written as c 0 2 + 1 = ( 1 a 0 2 ) ( 1 b 0 2 ) c_0^2 + 1 = (1 - a_0^2)(1 - b_0^2) If c 0 c_0 is odd, then c 0 1 ( m o d 4 ) c_0 \equiv 1 \pmod{4} and 1 a 0 2 , 1 b 0 2 0 or 1 ( m o d 4 ) 1 - a_0^2, 1 - b_0^2 \equiv 0 \text{ or } 1 \pmod{4} so the equation becomes 2 c 0 2 + 1 = ( 1 a 0 2 ) ( 1 b 0 2 ) 0 or 1 ( m o d 4 ) 2 \equiv c_0^2 + 1 = (1 - a_0^2)(1 - b_0^2) \equiv 0 \text{ or } 1 \pmod{4} which is a contradiction, so we can conclude c 0 c_0 is even. Therefore, using the same form of the equation mod 4 4 again, we have 1 c 0 2 + 1 = ( 1 a 0 2 ) ( 1 b 0 2 ) ( m o d 4 ) a 0 2 0 b 0 2 ( m o d 4 ) a 0 , b 0 are even 1 \equiv c_0^2 + 1 = (1 - a_0^2)(1 - b_0^2) \pmod{4} \implies a_0^2 \equiv 0 \equiv b_0^2 \pmod{4} \implies a_0,b_0 \text{ are even}

Since each of a 0 , b 0 , c 0 a_0,b_0,c_0 is even and at least one is nonzero, there is some positive integer k k such that 2 k 2^k divides each of a 0 , b 0 , c 0 a_0,b_0,c_0 and at least one of the following is odd: a 1 = a 0 2 k , b 1 = b 0 2 k , c 1 = c 0 2 k . a_1 = \frac{a_0}{2^k}, \qquad b_1 = \frac{b_0}{2^k}, \qquad c_1 = \frac{c_0}{2^k}.

Using these new values, the given equation becomes a 1 2 + b 1 2 + c 1 2 = 4 k a 1 2 b 1 2 a_1^2 + b_1^2 + c_1^2 = 4^k a_1^2 b_1^2

Since k k is positive, 4 k 0 ( m o d 4 ) , 4^k \equiv 0 \pmod{4}, so a 1 2 + b 1 2 + c 1 2 = 4 k a 1 2 b 1 2 0 ( m o d 4 ) a 1 b 1 c 1 0 ( m o d 2 ) a_1^2 + b_1^2 + c_1^2 = 4^k a_1^2 b_1^2 \equiv 0 \pmod{4} \implies a_1 \equiv b_1 \equiv c_1 \equiv 0 \pmod{2} but then none of a 1 , b 1 , c 1 a_1, b_1, c_1 is odd, contradicting the definition of k . k.

This final contradiction is only under the assumption that there is some nonzero integral solution, so we can conclude that there is no such solution. In particular, there is no solution using positive integers.

Thank you, nice solution.

Hana Wehbi - 2 years, 10 months ago

Thank you for pointing out my errors since I made up mind to show that exist no such Pythagorean thagorean triplets however, I came up with wrong ideas about the triplets. I guess your solution is based on the infinite descent.

Naren Bhandari - 2 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...